Den tidiga bosättningen i Kemi älvdal - några huvuddrag. - Vahtola, Jouko (1980)
Summary: Outstanding features of early settlement in the Kemi river valley.
jufo
Keywords: paikannimet -- asutushistoria -- suomen kieli -- Kemijokilaakso; nimistöntutkimus; place names -- history of settlement -- finnish -- Kemi river valley; onomastics